Use of mesoglycan in the acute phase of hemorrhoidal disease (the CHORMES study): study protocol for a double-blind, randomized controlled trial - Gaetano Gallo; Arcangelo Picciariello; Alberto Realis Luc; Antonella Salvatore; Angelo Di Vittori; Marcella Rinaldi; Mario Trompetto (Trials)
Abstract Background Hemorrhoidal disease (HD) is associated with substantial economic burden and negative effects on health-related quality of life (HRQoL). The aCute HaemORrhoids treatment with MESoglycan (CHORMES) study aims to evaluate the effects of orally administered mesoglycan, a natural preparation of glycosaminoglycans with antithrombotic and profibrinolytic properties, as an acute treatment in patients with HD. Methods CHORMES is a phase 2, double-blind, randomized controlled trial being conducted at two centers in Italy. Adults aged 18–75 years with Grade I–III HD according to Goligher classification or external thrombosed hemorrhoids, and a Hemorrhoidal Disease Symptom Score (HDSS) of ≥ 5, will be randomly allocated in a 1:1 ratio to mesoglycan or placebo and will be treated for 40 days (two capsules for the first 5 days and one capsule for the subsequent 35 days twice daily [after breakfast and dinner], equivalent to 200 mg in the first 5 days and 100 mg subsequently). Concomitant use of analgesics is permitted in both treatment groups. The trial aims to enroll 50 patients, with 25 patients in each treatment group. The primary objective of the trial is to evaluate the efficacy of mesoglycan in reducing symptoms of HD, assessed via change in HDSS from baseline (day 0) to day 40 in the intention-to-treat population. Secondary objectives include changes in HRQoL from baseline to day 40 using the Short Health Scale for Hemorrhoidal Disease, safety (adverse effects, physical assessments, vital signs and laboratory parameters in the safety population), fecal continence assessed using the Vaizey score, bleeding assessed using the Bleeding score, the amount and type of analgesic taken, and pain. Patient enrolment began on 11 December 2023, and trial completion is expected by December 2024. Discussion The CHORMES trial will evaluate the efficacy and safety of mesoglycan, in addition to its impact on HRQoL, analgesic use and pain, in patients with HD. The results of the trial will assist clinicians in determining the most effective treatment for patients with HD. Trial registration ClinicalTrials.gov NCT06101992. Prospectively registered on 26 October 2023 at https://clinicaltrials.gov/ct2/show/NCT06101992 .